CITREX 2019 promotes innovative culture among young researchers - UMP, PNC (2019)
The Creation, Innovation, Technology and Research Exposition (CITREX) 2019 has entered into its ninth edition with Universiti Malaysia Pahang (UMP) seen as a platform that promotes and nurtures innovative culture among researchers, be it the academic staff or students.